TRADISI ILMIAH DAN KEJAYAAN ILMU PENGETAHUAN DALAM ISLAM - Abdurrahman; Budi Handrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the scientific tradition and the glory of science in Islamic civilization through a qualitative approach with library research methods. Throughout its history, Islamic civilization has made significant contributions to the development of science in various fields, including mathematics, astronomy, medicine, and philosophy. This study collects and analyzes relevant literature to understand how the scientific tradition in Islam developed and how these contributions influenced the world of science globally. The results of the study indicate that the scientific tradition in Islam is driven by religious values ​​that encourage the search for knowledge and science. In addition, this study also reveals that the glory of science in Islam is not only limited to the golden age, but also has a continuing impact until today. These findings are expected to provide new insights into the importance of the scientific tradition in Islam and its relevance in the modern context.